Global Forecasting Confirmed and Fatal Cases of COVID-19 Outbreak Using Autoregressive Integrated Moving Average Model - Dansana, Debabrata; Kumar, Raghvendra; Das Adhikari, Janmejoy; Mohapatra, Mans; Sharma, Rohit; Priyadarshini, Ishaani; Le, Dac-Nhuong (Frontiers in Public Health, 2020)
The world health organization (WHO) formally proclaimed the Coronavirus, called COVID-19 episode a worldwide pandemic on 11 March 2020. In December 2019 COVID-19 was found in Wuhan city, China, and now coronavirus has spread over various nations as the flare-up has now spread to 198+ nations. All out contaminations outside of China are quickening exponentially, with the worldwide disease cost outperforming 250,000+ as of 18 March 2020, with Asia's commitment at more than 81,000. The Proposed model is using time series analysis to forecast the outbreak of COVID-19 in the world in upcoming days by using an autoregressive integrated moving average(ARIMA).Data has been taken from 1 February 2020 to 1 April 2020 and the outcome showed good performance, around 120000 confirmed fatalities cases has been forecasted using ARIMA model till 1 April 2020 apart from that we have evaluated total confirmed cases, total fatalities cases, autocorrelation function and white noise time-series for both confirmed and fatalities case of COVID-19 outbreak.